Impact of E-learning Tools (Moodle, Microsoft Teams, Zoom) on Student Engagement and Achievement at Jordan Universities - Khrisat, Zaid; Fakhouri, Hussam N. (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study examines the impact of digital learning platforms—Moodle, Microsoft Teams, and Zoom—on student engagement and academic achievement at the University of Jordan. The study explores students’ familiarity with these e-learning tools and their effect on self-directed learning and performance. Over three months, data was collected from 450 students through an online questionnaire comprising closed questions. The analysis employed multiple regression models to consider variables such as gender, age, prior computer literacy, attitude towards emerging technology, learning preferences, and the implementation of e-learning within the university. Additionally, a qualitative content analysis identified the advantages and disadvantages of e-learning from the students’ perspectives. The findings indicate that strategic implementation of e-learning platforms significantly influences student perceptions more than individual contextual factors. Students appreciated the connectivity and accessibility provided by these platforms. Those with prior computer knowledge and those studying emerging technologies showed a particularly positive attitude towards e-learning. The study concludes that engagement with e-learning tools markedly enhances self-study habits and academic performance, underscoring the importance of integrating digital platforms into educational strategies.